Potensi Medication error Pada Resep di Salah Satu Apotek di Kota Kadipaten: Potential Medication Error on Prescription at One Pharmacy in Kadipaten City - Ida Lisni; Nurani Eka Gumilang; Eva Kusumahati (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Medication errors can occur in each process, at prescribing, transcribing, dispensing, and administration processes. This study is to find out that the prescribing stages have met the legality principle by the RI Minister of Health Regulation Number 73 of 2016 and continued with the determination of the Medication Error Index (NCC MERP). This research method is non-experimental observational. The research was conducted by collecting prescriptions for the period July - December 2019 retrospectively. The sample size in the study was determined by a systematic random sampling technique based on the Slovin formula. 1,581 prescriptions were obtained and the results of the samples taken were 352 prescriptions. The results showed that there were prescriptions that did not meet the administrative requirements were 17.9%, did not meet the pharmaceutical requirements of 44.9%, and those that did not meet the clinical requirements were 7.5%. The results of the analysis of the characteristics of the Medication Error Index for category C were 68%, category D was 0.5%, and category E was 1.8%. Keywords : Pharmacy; Prescription; Medication Error